Neurofeedback Technology Reduces Cortisol Levels in Bruxismitle Patients: Assessment of Cerebral Activity and Anxiolytic Effects of Origanum majorana Essential Oil - José Joaquín Merino; José María Parmigiani-Izquierdo; Adolfo Toledano Gasca; María Eugenia Cabaña-Muñoz (Biomimetics)
Cerebral activities were measured during 21 essions in NeurOptimal (NO)-trained patients with bruxism. Salivary cortisol levels were quantified for each six training sessions (session 1, 6, 12, 18, 21) in 12 patients with bruxism after performing their pre- and post-NeurOptimal sessions. Their cortisol levels were compared with controls (without stress). We evaluated whether NO overtraining could reduce stress in bruxism after 21 repeated sessions with/without Origanum majorana inhalation by using nasal impregned filters with this essential oil (n = 12). This study enrolled 89 participants (590 salivary samples for cortisol assessment by ELISA ng/mL). Salivary samples were collected at several NO learning sessions (session 1, 6, 12, 18, and 21). In the present study, we assessed whether Origanum majorana essential oil exposure during 21 NO training sessions can promote anxiolytic effects by reducing cortisol levels in Bruxismitle patients or modulate their brain activities. The experimental design also included control subjects without NO training (n = 30) and unstressed participants without bruxism, as well as trained NeurOptimal (n = 5) participants during the 21 sessions, also including control subjects without stress. In our study, NeurOptimal post-training decreased cortisol levels in Bruxismitle patients, reducing stress scores on the Hamilton II scale after 21 NO sessions; finally, Origanum majorana essential oil exposure during NO training could enhance anxiolytic effects of repeated NO in Bruxismitle patients. The parameter divergence as an index of cerebral activity evaluates the reached difference between cerebral activity at pre-learning (PRE) minus post-training (POST) values in Bruxismitle participants with/without Origanum majorana odor exposure during each NO training sessions. As a consequence of NO overtraining, these cerebral activities fluctuate reaching a calm state while anxious states are associated with high divergences. The reduction in divergences when they are close to zero by habituation means a final calm state is reached by NO overtraining, while higher divergences mean anxiogenic states. Collectively, Origanum majorana essential oil inhalation during NO training could decrease salivary cortisol levels after 21 NO training sessions in Bruxismitle.